Health tourism: a study on tourists’ motivational factors in choosing Melaka as a health tourism destination / Siti Hajar Ramlee, Nurul Atiqah Adziz and Shahidah Juliana Mohamad Shahid - Ramlee, Siti Hajar; Adziz, Nurul Atiqah; Mohamad Shahid, Shahidah Juliana (Faculty of Hotel and Tourism Management, 2013)
Travelling around the globe for health treatment is becoming more and more prevalent these days. The fundamental premise of health tourism is that the same care, or even better quality of care, may be available in other countries, and obtained at a more affordable cost than in the home country (Medical Tourism Association, 2008). Although many theories on the potential of health tourism in Malaysia have been reported in the general media, there is a lack of adequate empirical evidence on the subject. Melaka, as one of the several major destinations in health tourism industry that is rapidly developing, is creating worldwide trademark as “The Medical Hub of Asia”. The objective of this study is to identify the motivational factors that motivate tourists to choose Melaka as a health tourism destination. Health tourism is largely a consumerdriven trend and in order to survive and thrive, the health-delivery industry must keep up with its consumers' demands and needs (Nakra, 2011). This study was carried out at three private hospitals around Banda Hilir and Ayer Keroh with a sample size of 120 health tourists. The six motivational factors identified and ranked according to importance are products offerings, demographic profiles, hospital services, hospital facilities, medical expertise and health service costs and cultural similarity. Simultaneously, the findings can be used by the hospitals, Melaka State Government and tourism related organizations in order to develop successful marketing strategies that further promote Melaka as a chosen health tourism destination. Further exploration is required in the area of health tourists’ motivational factors. In this study, it was found that the most influencing motivational factor is products offerings. However, the contributing factors that motivate tourists in choosing Melaka as a health tourism destination are hospital services and hospital facilities.